Preparation of Chiral Epoxy Resins and the Optically Active Cured Products - Xinyuan Tang; Ming Hu; Xiaoran Liu; Yanyun Li; Junying Zhang; Jue Cheng (Advances in Polymer Technology)
Chirality is one of the most common and significant phenomenon in nature, and epoxy resin is one of the most widely used and researched thermosetting resins, however the influences of chiral carbon in epoxy group on the performances of the cured epoxy resins have ever been hardly studied, therefore it is crucial and meaningful to explore the structure–function relationship of chirality and performance of epoxy resins. Herein, from the analysis of synthesis mechanism, the different chiral configuration with high percent enantiomeric excess (>99%) and racemic bisphenol A epoxy resins were simply prepared by controlling the chirality of epichlorohydrin. The apparent activation energy of the curing process with D230 was calculated by Kissinger method and Flynn–Wall–Ozawa method, respectively, and both results indicate that chirality have no effect on the curing reaction. We found that the secondary structure of epoxy monomer is untouched by its chirality, and they are all right helix structure. For this reason, the thermal stability, glass transition temperature, and thermomechanical properties of diverse chiral epoxy resins cured by D230 have no significant difference. Nevertheless, it was found that the optical rotation activity of chiral epoxy resins can be partially maintained after curing reaction, it manifests the cured products of chiral epoxy resins possesses the possibility of application in the field of polarized materials.